Analysis of Bifurcation and Stability on Solutions of a Lotka-Volterra Ecological System with Cubic Functional Responses and Diffusion (Communications in Mathematical Research, 2021)
This paper deals with a Lotka-Volterra ecological competition systemwith cubic functional responses and diffusion. We consider the stability of semi-trivial solutions by using spectrum analysis. Taking the growth rate as a bifurcationparameter and using the bifurcation theory, we discuss the existence and stability ofthe bifurcating solutions which emanate from the semi-trivial solutions.
Keywords: Lotka-Volterra ecological system; stability; bifurcating solution.